Improving the performance of ultrasound transducer using simulation and modeling: تحسين أداء محول طاقة الأمواج فوق الصوتية باستخدام المحاكاة والنمذجة - Rama Abd Rabouh Mahsoun, Yasser Estanbouli (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2022)
Improving medical imaging using ultrasound is important in order to get a high- resolution medical image, this research aims to achieve a physical modeling and simulation of an ultrasound transducer (UT) showing the electrical impedance of the piezoelectric material, in order to increase the transducer performance at both high and low frequencies by choosing a suitable piezoelectric material with good impedance. we adopted in this research Lead Zirconate Titanate material (PZT4), and performed modeling using mathematical equations that describe the actual physical behavior in the transducer structure and made a graphic user interface (GUI) using Matlab environment that demonstrate it, and display the electrical impedance of the piezoelectric material. As well as using Simulation by Finite Elements Methods (FEM) using On Scale environment and comparing the results in both of them. The results matched at a certain frequency, to give a clear image in the deep areas of the body. This later enables us to make modifications to the transducer structure and add backing layer and matching layer for the piezoelectric material.